The Maqashid Syari'ah Perspective on The Subsistence Obligations by "Fathers" Against Children Due to Adultery: (An Analysis of MUI Fatwa Number 11 f o2012 About the Situation of and How to Treat a Child Born Out of Adultery) - Alfajar Nugraha; Asmuni Asmuni (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2024)
The accommodation of the clause "civil relations" by the Constitutional Court Number 46/PUU-VIII/2010 became a polemic because it showed a relationship between "fathers" and their biological children and indirectly "legalizes" the relationship both with no marriage process. Seeing the MUI as one of Indonesia's Islamic institutions provided a firm interpretation with interpretation that it still negated the lineage relationship between the "fathers" and their biological children, and the fall of rights and obligations is due to the punishment of "fathers," not the "fathers" and children ties. as stated in the MUI fatwa No. 11 of 2012, but a question arises as to whether the fatwa is in accordance with the provisions of the Shari'a. Therefore, later in this article, we would analyze descriptively and analytically the linkages of the MUI fatwa mentioned above with the construction of shari'ah provisions through the maqashid shari'ah aspect. The results of this study can be concluded that the MUI fatwa Number 11 of 2012 has fulfilled the maqashid syari'ah aspect as the construction of kulliyatul al khams asy syatibi, with the dharuriyat level category in the context of hifz nafs and hifz nasl as a form of protection and prevention of neglect, especially by giving ta'zir punishment to men who cause birth to meet their needs and as a form of syadz al-dzari'ah adultery in the context of not linking the lineage of "fathers" to their biological children as protection against honor and descendants for a person as a human being who is glorious.